COMPARATIVE ANALYZES OF SINGLE-ROD AND DOUBLE ROD FIXATION FOR ANTERIOR «BONE ON BONE» FUSION - PetrenkoD.Е. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Using finite element method comparative analyzes of the stress-strain distribution of the single-rod and double-rod instrumentation for anterior «bone on bone» spinal fusion was done. It was revealed that the most loaded zones of the «thoracic spine-implant system» are rods and anterior parts of the vertebral bodies at the apex of the kyphosis. Close contact of the vertebral bodies in instrumented spine spares physiologic loading of the spine.